Peningkatan Hasil Belajar Biologi Siswa Kelas X MIPA 1 SMA Negeri 1 Watampone Melalui Pembelajaran Kooperatif STAD Dengan Menggunakan Kartu Indeks - Sitti Aisyah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2019)
This research is Classroom Action Research which aims to improve student learning outcomes through STAD Cooperative Learning Using Index Cards. The subjects of this study were students of class X MIPA 1 Watampone 1 Senior High School totaling 36 people in the 2016/2017 academic year. The implementation of this study consisted of two cycles. The collected data is analyzed using qualitative and quantitative analysis. The results are after two tests of the class average value of 64, 21 in the first cycle increased to 77.02 in the second cycle, this means that the standard of graduation at SMA 1 Watampone has been achieved with the number of students as many as 26 people. The number of students who completed individually in the first cycle was 11 people increased to 24 people in the second cycle. Classically, the increase was 42.30% in the first cycle which increased to 92.30% in the second cycle. Thus, STAD Cooperative Learning Using the Index Card as a learning model is able to improve student learning activities and outcomes, especially students' biological understanding.